AGRESIVITAS PAJAK PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Hendi Prihanto; Kurnia Sari Dewi; Nirwan Mulyatno; Frans Augusta Adipermana (Universitas Prof. Dr. Moestopo (Beragama), 2022)
This study aims to analyze the effect of debt level, profitability, firm size, leverage, capital intensity and disclosure of corporate social responsibility on tax aggressiveness behavior in Manufacturing Companies listed on the Indonesia Stock Exchange (IDX) in the 2015 - 2017 period as many as 117 samples of financial statements with using a saturated sampling technique (census), after verification of the manufacturing companies that meet the feasibility, which is processed by an analytical method using logistic regression test. The results showed that the level of debt, profitability, firm size, leverage, capital intensity and the implementation of Corporate Social Responsibility together had a significant effect on tax aggressiveness. Partially, this study shows that capital intensity has a positive and significant effect on tax aggressiveness. While the level of debt, profitability, company size, corporate social responsibility does not have a significant effect on tax aggressiveness.